Keefektifan metode Penerjemah Tata Bahasa untuk kemampuan menulis siswa - Akhmad Nuris Hidayat; Lutfiah; Fahril Nolan Giraldo (Mastery: Master of English Language Journal, 2025)
The purpose of this study is to look into how the Grammar Translation Method (GTM) affects students' writing abilities. The usefulness of GTM in improving writing abilities is still up for question, but it has been widely utilized in language training since it places an emphasis on sentence translation and the application of grammatical rules. A sample of students who were taught utilizing GTM was included in the quantitative study design. To gauge the extent to which students' writing abilities had improved, pre- and post-test evaluations were carried out with an emphasis on coherence, sentence structure, and grammar accuracy. The findings showed those students' writing abilities, especially in terms of sentence structure and grammatical precision, had significantly improved. Nonetheless, there was less of an impact on pupils' capacity to generate concepts and write creatively. According to the results, even though GTM can improve writing's technical elements, but other techniques might be required to encourage students' writing's originality and concept growth.